2021
DOI: 10.1007/s00415-021-10708-1
|View full text |Cite
|
Sign up to set email alerts
|

Risk of multiple sclerosis relapses when switching from fingolimod to cell-depleting agents: the role of washout duration

Abstract: Background Fingolimod (FTY) induces sequestration of lymphocytes in secondary lymphoid organs and the average lymphocyte recovery following discontinuation takes 1-2 months. It has been hypothesized that the therapeutic effects of subsequent cell-depleting agents may be compromised if initiated before lymphocyte recovery has occurred. Objective To assess the risk of relapses following FTY discontinuation and the initiation of a B/T cell-depleting agent in relation to washout duration using data from the Italia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
0
5
1
Order By: Relevance
“…In contrast, impairment in disease control in patients switching from FTY to ocrelizumab was persistent during follow-up and thus far beyond the previously reported timespans. Whereas the abovementioned publications repeatedly identified the duration of washout as a risk factor for disease reactivation and/or disability worsening, 17 , 19 and were restricted to rather short follow-up, we here document impaired effectiveness of ocrelizumab in patients switching from FTY even after rebaselining to month 6 of ocrelizumab treatment.…”
Section: Discussioncontrasting
confidence: 43%
“…In contrast, impairment in disease control in patients switching from FTY to ocrelizumab was persistent during follow-up and thus far beyond the previously reported timespans. Whereas the abovementioned publications repeatedly identified the duration of washout as a risk factor for disease reactivation and/or disability worsening, 17 , 19 and were restricted to rather short follow-up, we here document impaired effectiveness of ocrelizumab in patients switching from FTY even after rebaselining to month 6 of ocrelizumab treatment.…”
Section: Discussioncontrasting
confidence: 43%
“…On the other hand, and in line with aspects presented above, a longer washout period could lead to recovery from lymphopenia before initiation of cell-depleting agents, which may limit the risk of therapies being ineffective. Interestingly, a recent study by Ferraro et al [49] in this journal showed that extending the washout period prior to commencing cell-depleting agents does not positively affect outcome parameters in the long term. In this study, the risk of relapse increased with the washout duration when switching from fingolimod to a lymphocyte-depleting agent (including cladribine, alemtuzumab, rituximab and ocrelizumab) during the 22 months of follow-up.…”
Section: Possible Mechanisms Of Compromised Efficacy and Resulting Management Considerationsmentioning
confidence: 95%
“…Previous studies clearly demonstrated that MS disease reactivation is frequent and could be acute after fingolimod withdrawal. 14 - 16 Recent studies specifically assessed the switch from fingolimod to BCDT 4 - 6 , 17 and found a long washout period in patients switching from fingolimod to BCDT associated with risk of relapse. Zhong et al 6 reported a higher risk of relapse within the first 3 months of OCR for patients switching from fingolimod with a mean washout period of 48.5 days than for patients who previously received another DMT.…”
Section: Discussionmentioning
confidence: 99%
“… 1 - 8 However, real-life studies noted that the risk of disease activity after switching to BCDT may be unequal depending on the prior DMT. 4 - 7 , 9 , 10 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation